2015
DOI: 10.1155/2015/546497
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Test-Retest Reliability of New Thermographic Technique Called Thermovision Technique of Dry Needling for Gluteus Minimus Trigger Points in Sciatica Subjects and TrPs-Negative Healthy Volunteers

Abstract: The aim of this study was to assess the validity and test-retest reliability of Thermovision Technique of Dry Needling (TTDN) for the gluteus minimus muscle. TTDN is a new thermography approach used to support trigger points (TrPs) diagnostic criteria by presence of short-term vasomotor reactions occurring in the area where TrPs refer pain. Method. Thirty chronic sciatica patients (n=15 TrP-positive and n=15 TrPs-negative) and 15 healthy volunteers were evaluated by TTDN three times during two consecutive days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 32 publications
3
34
0
Order By: Relevance
“…Several authors have affirmed that the skin temperature of the MTrP area should not be used to detect or diagnose MTrPs. Measurement with the thermovision technique of active MTrPs located in the gluteus minimus indicated an increase in their temperature after treatment with DDN in patients with chronic sciatica [67]. Previously, Skorupska et al [68,69,70] found that the presence of short-term vasodilatation after DDN suggested the involvement of sympathetic nerve activity in the myofascial pain presented in patients with sciatica.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have affirmed that the skin temperature of the MTrP area should not be used to detect or diagnose MTrPs. Measurement with the thermovision technique of active MTrPs located in the gluteus minimus indicated an increase in their temperature after treatment with DDN in patients with chronic sciatica [67]. Previously, Skorupska et al [68,69,70] found that the presence of short-term vasodilatation after DDN suggested the involvement of sympathetic nerve activity in the myofascial pain presented in patients with sciatica.…”
Section: Discussionmentioning
confidence: 99%
“…2 The prevalence of gluteal syndrome, which is a CS-related subtype of myofascial pain syndrome, has been estimated to occur in approximately 30% of LBLP patients. 7,8 Myofascial pain syndrome is defined as a local pain syndrome characterized by (i) the presence of trigger points, ie, limited sites of severe muscle tenderness or hypersensitivity, (ii) a determined area of referred pain, and (iii) characteristic motor, sensory, and autonomic dysfunctions and symptoms. 9 The location of the referred pain is incompatible with the innervation and dermatomes at the site.…”
Section: Introductionmentioning
confidence: 99%
“…A similar observation was provided in our previous studies on a minimally invasive procedure applied to patients with both LBLP and MPS. 7,8 A subpopulation of MPS-positive LBLP patients presented with a needle-provoked immediate vascular reaction covering approximately 30% of the skin of the lower limb within the perceived pain area. Moreover, an average temperature increase of approximately 1°C was confirmed, which can be used to visualize the results 7,8 (video file).…”
Section: Introductionmentioning
confidence: 99%
“…For typical thermal images, each pixel is calibrated and its temperature value is given with specified accuracy which depends on the used thermal camera type. For this reason, the range of ​​analysis and image processing methods is narrowed to those that interfere the least with the calibrated pixel values falsifying the local temperature distribution . This directly affects the selection of the analysis and image processing methods described below.…”
Section: Methodsmentioning
confidence: 99%